Characterization of virulence pattern in Rhizoctonia solani causing sheath blight of rice - and VIVEK SINGH, MEHI LAL*, JANKI KANDHARI (Indian Phytopathology, 2012)
Sheath blight (Rhizoctonia solani Kühn) of rice is an important disease in India. To determine the virulence diversity of isolates, total six cultivars of rice were artificially inoculated with 25 isolates of R. solani in glass house. Three susceptible (Pusa Basmati-1, Annapurna, Swarna) and three tolerant (Pankaj, Manasarovar, Swarnadhan) cultivars were tested against all isolates. All isolates were pathogenic on six cultivars except isolate RS-25 pathogenic, which was pathogenic on four cultivars and non-pathogenic on two cultivars namely, Manasarovar and Swarnadhan. On the basis of virulence reaction on different cultivars, the isolates were categorized into four groups; highly virulent, moderately virulent, less virulent and avirulent. Maximum relative lesion size on cultivars PB-1, Annapurna, Swarna, Pankaj, Manasarovar and Swarnadhan was observed as 69.66 with RS-21, 72.74 with RS-5, 65.09 with RS-16, 65.43 with RS-17, 59.09 with RS-18 and 61.87 with RS-6 respectively. Maximum virulence index of 7.33 was at par in RS-16 and RS-18 and maximum susceptibility index was found on cv. Annapurna (7.76). Four isolates viz, RS-16, RS-18, RS-20 and RS-21 can be used in future for screening for resistance against sheath blight of rice.